PARTISIPASI PETANI DAN KEBERHASILAN PROGRAM PENGEMBANGAN USAHA PANGAN MASYARAKAT (PUPM) DI KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Resti Anggraini; Kordiyana K Rangga; Tubagus Hasanuddin (Lampung University, 2019)
The purpose of this research is to know the level of farmers’ participation, the factors associated with the level of farmers’ participation and the relationship between the level of farmers’ participation and the success of the program. Data of this research were collected in February-March 2018. The respondents are 66 rice farmers members of farmer groups joining the program who are chosen randomly The research is a survey and data are analyzed using Rank Spearman and descriptively. The results showed that the level of farmers’ participation is in a low catergory. Factors related to the level of farmers’ participation in PUPM program are farmers’ knowledge on the program, frequency of their participation in extension activities, and level of farmers’ cosmopolitan character. There is a significant relationship between farmers’ participation and the success of PUPM program in Palas Subdistrict of South Lampung Regency. Key words: farmer, participation, program, PUPM